2002
DOI: 10.1002/pola.10569
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the cumulative degree of polymerization for the dead‐end polymerization of styrene

Abstract: This article explores the use of a new relation correcting theoretical (DPn) with experimental values obtained in the dead-end polymerization of styrene with azocompound. The syntheses were realized for several starting initiator-to-monomer ratios (C 0 's); values comprised between 10 and 0.1%, and the experimental (DPn) were obtained by size exclusion chromatography. Concerning the theoretical (DPn), a new relation is proposed considering the loss of initiating radicals [I ⅐ ] used in primary termination and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The method for the calculation of (DP n ) cum consists of a divided conversion of the reaction into several intervals i (where i is an integer number) equal to b ( b is a constant), with the assumption that in each interval ( i − 1) b to ib , the reaction is isomolecular 40. The (DP n ) cum value is then given by the various (DP n ) i values of each interval according to eq.…”
Section: Resultsmentioning
confidence: 99%
“…The method for the calculation of (DP n ) cum consists of a divided conversion of the reaction into several intervals i (where i is an integer number) equal to b ( b is a constant), with the assumption that in each interval ( i − 1) b to ib , the reaction is isomolecular 40. The (DP n ) cum value is then given by the various (DP n ) i values of each interval according to eq.…”
Section: Resultsmentioning
confidence: 99%
“…Polymerization reactions of monomers such as MMA and acrylamide end by termination by a disproportionation mechanism, and the consequent materials are mainly composed of diblock structures, rather than triblocks. However, the utilization of high initiator concentrations can direct reactions toward termination by a combination mechanism 26–30. Boutevin et al29 successfully showed that the utilization of high initiator concentrations leads to termination by combination even for polymerizations of monomers that do terminate by a disproportionation mechanism under ordinary conditions.…”
Section: Resultsmentioning
confidence: 99%